Kinerja Waktu Pelaksanaan Proyek Pekerjaan Jalan Di Kabupaten Kolaka Utara (Studi Kasus Jalan Poros Lasusua Desa Totallang) - Sufrianto, Sufrianto; Ilham, Vickky Anggara; Makkawaru, Andi; Ilahi, La Ode Altakdir (Universitas Sulawesi Tenggara, 2024)
The aim of the research is to find out or predict how much a project will cost during implementation and to find out the effectiveness of project control using the Earned Value Method. To overcome existing problems, an Earned Value method is used. There are two parameters or indicators used for analysis, namely BCWS, BCWP. Delay deviations can be identified by looking at the Schedule Variance (SV). This method can also be used to determine the efficiency of resource use in the form of the schedule performance index (SPI). The project implementation time aspect has a negative value up to the 12 th week of (SV) -Rp. 44,776,771.84 or schedule performance index (SPI) = 0.82 < 1. The calculation results are obtained from an effectiveness value of 0.85 for controlling project time using the Method Earned Value. In other words, the results of an effectiveness value that is smaller than 1 (one) can be said to be that the Time Performance for the Implementation of the Concrete Pavement Road Work Project in North Kolaka Regency is less effective. From the results of the time performance study using the Earned Value Method, it can be concluded that the Time Performance for the Implementation of the Concrete Pavement Road Work Project in North Kolaka Regency experienced a delay from the initial plan. It is clear that in weeks 1 to 12 the project performance was delayed from the planned schedule